Strategic intervention towards sports facilities management performance / Mohd Asrul Hassin - Hassin, Mohd Asrul (2024)
Facilities Management (FM) is a profession that integrates people, place, process, and technology to ensure functionality, comfort, safety, and efficiency in the built environment. Performance Management (PM) assesses success against goals and provides information on resource transfer, efficiency, and performance. Malaysia's FM industry is still in its infancy and requires development to compete globally. Strategic intervention problems in Malaysia include inconsistent decision-making, service, lack of knowledge, financial analysis, safety and an ageing structure. The purpose of this study is to look at the role of Strategic Intervention (SI) in sports facilities management performance. This research aims to propose a strategic intervention for improving the performance of sports FM. The first research objective is to identify the strategic intervention indicators for improving strategic sports facilities' performance. The second research objective is to determine the relationship between identified strategic intervention indicators and strategic sports FM performance. Finally the third research objective is to develop a model of strategic intervention in improving strategic sports FM performance. This research specifically focused on the entire 29 football stadiums. This study used positivism paradigm, a deductive methodology, and survey strategies. The conceptual framework was created using strategic facilities management theory and a thorough analysis of the current literature. This phase's findings established the first SI that will be studied further in the second phase of this investigation. The major technique of data collecting is a questionnaire delivered during the survey. The information was gathered from Malaysia's 29 football stadiums. To fulfil the second and third aims of this study, the data were originally analysed using the Statistical Package for Social Science (SPSS 23) for factor analysis and Structural Equation Modelling (SEM-PLS 3.0). Based on the findings from the literature, the final Strategic Intervention Model was created and further analysed using SPSS and SEM-PLS. The model finds that there is a substantial link between Operational Facilities Management (OFM), Services Internal, Finance (FIN) and Customers (SIC). External Customers (SEC) and Technology (TEC) have a minor impact on the created model. After that the expert validation proses was conducted to verify the research model. The finding of the research found only three variables are significance for strategic intervention model consist of OFM, FIN and SIC towards performance of sports facilities. As a result, the final model might serve as a reference for policymakers, practitioners, and stadium management. The created model will aid in the overall improvement of sports facilities management performance. By understanding the SI in Sports Facilities Management Performance, our studies have helped to bridge a knowledge gap.